International law and world order : a critique of contemporary approaches / B.S. Chimni, Jawaharlal Nehru University. - Chimni, B. S., 1952- (Cambridge University Press, 2017)
" ... Articulates an Integrated Marxist Approach to International Law (IMAIL) combining the insights of Marxism, socialist feminism and postcolonial theory. The book uses IMAIL to systematically and critically examine the most influential contemporary theories of international law including new, feminist, realist and policy-oriented approaches. In doing so, it discusses a range of themes relating to the history, structure and process of international law. The book also considers crucial world order issues and problems that the international legal process has to contend with, including the welfare of weak groups and nations, the ecological crisis and the role of human rights."--Page [i].